Cortical Excitability, Synaptic Plasticity, and Cognition in Benign Epilepsy With Centrotemporal Spikes: A Pilot TMS-EMG-EEG Study. Issue 2 (March 2020) - Baumer, Fiona M.; Pfeifer, Kristina; Fogarty, Adam; Pena-Solorzano, Dalia; Rolle, Camarin E.; Wallace, Joanna L.; Rotenberg, Alexander; Fisher, Robert S.
Abstract : Purpose: Children with benign epilepsy with centrotemporal spikes have rare seizures emerging from the motor cortex, which they outgrow in adolescence, and additionally may have language deficits of unclear etiology. We piloted the use of transcranial magnetic stimulation paired with EMG and EEG (TMS-EMG, TMS-EEG) to test the hypotheses that net cortical excitability decreases with age and that use-dependent plasticity predicts learning. Methods: We assessed language and motor learning in 14 right-handed children with benign epilepsy with centrotemporal spikes. We quantified two TMS metrics of left motor cortex excitability: the resting motor threshold (measure of neuronal membrane excitability) and amplitude of the N100-evoked potential (an EEG measure of GABAergic tone). To test plasticity, we applied 1 Hz repetitive TMS to the motor cortex to induce long-term depression-like changes in EMG- and EEG-evoked potentials. Results: Children with benign epilepsy with centrotemporal spikes tolerate TMS; no seizures were provoked. Resting motor threshold decreases with age but is elevated above maximal stimulator output for half the group. N100 amplitude decreases with age after controlling for resting motor threshold. Motor cortex plasticity correlates significantly with language learning and at a trend level with motor learning. Conclusions: Transcranial magnetic stimulation is safe and feasible for children with benign epilepsy with centrotemporal spikes, and TMS-EEG provides more reliable outcome measures than TMS-EMG in this group because many children have unmeasurably high resting motor thresholds. Net cortical excitability decreases with age, and motor cortex plasticity predicts not only motor learning but also language learning, suggesting a mechanism by which motor cortex seizures may interact with language development.